PEMBENTUKAN SET JALUR ALIRAN PROGRAM MENGGUNAKAN TEKNIK JUMLAH JALUR MINIMUM DAN TEKNIK JUMLAH PREDIKAT MINIMUM - Rosa de Lima Endang Padmowati (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2009)
Structured testing is based on the control flow of programs. The analysis of the control flow of program is conducted on a reduced flowgraph, called a decision-to-decision graph (DDGraph). The relations of dominance and implication between arcs enable to immediate identification of a subset of DDGraph arcs. These arcs are called unconstrained arcs, which have a property that, when the unconstrained arcs are exercised, the traversal of all the other arcs are guaranteed. In order to find a path cover for given program flowgraph, there are two methods: minimum number of paths technique and less pred technique.